Protective factors for mortality among HIV-positive people who inject drugs (PWID) in Malaysia. - Ramlan, Aida Roziana; Mohamed Nazar, Nor Ilyani; Ab Rahman, Norny Syafinaz; Muhamad, Dzawani; Zin, Che Suraya (Kulliyyah of Pharmacy, 2022)
Introduction: People who inject drugs (PWID) have long been associated with HIV transmission in the community. In many countries, Methadone Maintenance Therapy (MMT) programme has been regarded as a critical platform to ensure HIV-positive PWID receive appropriate antiretroviral treatment. Despite treatment availability and accessibility in Malaysia, mortality was extensively observed, and the protective factors are still scarcely studied in this population. This study investigated the protective factors for mortality among HIV-positive PWID in Malaysia's two mainstream treatment settings. Method: This was a retrospective cohort study. The data was collected from one HIV Clinic of a tertiary hospital and six (6) MMT programs of primary care clinics in the district of Kuantan, Pahang, from 2006-2019. The patients were categorised into three different subgroups. The mortality was recorded until the end of the study period. The survival rate was analysed using one-way ANOVA, and the associated factors were analysed using Cox proportional hazard regression analysis. Results: In total, 141 records were found to have met the inclusion and exclusion criteria. Fifteen HIV-related mortalities were recorded throughout the study period. There were significant differences in survival years between the MMT-only group versus MMT + ART and the MMT-only group versus the ART-only group (p-value <0.001 and 0.003, respectively). A longer ART duration was significantly associated with improved survival of PWID (HR=0.5, 95% CI=0.28-0.88). Extended duration in MMT program (HR= 0.50, 95% CI=0.33 – 0.78), started on ART (HR= 0.21, 95% CI=0.04 – 0.97) and received ART counselling (HR= 0.13, 95% CI=0.02 – 0.85) were significantly identified as protective factors for mortality among PWID on MMT. Conclusion: Three factors were identified as protective factors for mortality among HIV-positive PWID in Malaysia. Extended retention in the MMT programme, initiation of ART, and regularly receiving HIV-related counselling were the significant factors contributing to reduced mortality rates among the patients.